2020
DOI: 10.1177/0003319720977754
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Prognostic Value of Hematological Indices in Patients With ST Segment Elevation Myocardial Infarction: “A Head to Head” Analysis

Abstract: Although there are reviews and meta-analyses focusing on hematological indices for risk prediction of mortality in patients with ST segment elevation myocardial infarction (STEMI), there are not enough data with respect to direct to head-to-head comparison of their predictive values. We aimed to investigate which hematological indices have the most discriminatory capability for prediction of in-hospital and long-term mortality in a large STEMI cohort. We analyzed the data of 1186 patients with STEMI. In-hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
4
0
1
Order By: Relevance
“…It has previously been reported that high RDW is associated with increased incidence of CV diseases in the general population and that RDW is associated with poor prognosis in patients with established CV disease. 7,8,20,21 The present study demonstrated that RDW is significantly associated with coronary atherosclerosis, as measured by CACS. This association remained significant after adjustment for CV risk factors.…”
Section: Discussionsupporting
confidence: 60%
“…It has previously been reported that high RDW is associated with increased incidence of CV diseases in the general population and that RDW is associated with poor prognosis in patients with established CV disease. 7,8,20,21 The present study demonstrated that RDW is significantly associated with coronary atherosclerosis, as measured by CACS. This association remained significant after adjustment for CV risk factors.…”
Section: Discussionsupporting
confidence: 60%
“…14 Several studies reported that NLR was associated not only with CAD risk but also with CAD severity. 7,8,24,25 NLR was found to be a predictor of short-term 26,27 as well as long-term 28,29 prognosis in patients with myocardial infarction. In the overall population as well as in males of the present study, patients with CAD had higher WBC and neutrophil counts as well as NLR compared with non-CAD patients.…”
Section: Discussionmentioning
confidence: 91%
“…Notably, there are findings that high MHR is not associated with long-term outcomes in patients with CHD. Correlative studies have shown that a high MHR did not significantly increase case fatality [31]. This statistical result had a wide range of CIs and may be related to the small sample size for inclusion.…”
Section: Discussionmentioning
confidence: 96%